2015
DOI: 10.1152/physiolgenomics.00045.2015
|View full text |Cite
|
Sign up to set email alerts
|

AZT-induced mitochondrial toxicity: an epigenetic paradigm for dysregulation of gene expression through mitochondrial oxidative stress

Abstract: Koczor CA, Jiao Z, Fields E, Russ R, Ludaway T, Lewis W. AZT-induced mitochondrial toxicity: an epigenetic paradigm for dysregulation of gene expression through mitochondrial oxidative stress. Physiol Genomics 47: 447-454, 2015. First published July 21, 2015 doi:10.1152/physiolgenomics.00045.2015.-Mitochondrial dysfunction causes oxidative stress and cardiomyopathy. Oxidative stress also is a side effect of dideoxynucleoside antiretrovirals (NRTI) and is observed in NRTI-induced cardiomyopathy. We show here t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…It has been recently found that NRTIs altered nDNA methylation [41], and downregulated PPARγ and mtDNA-encoded genes expression [42]. Moreover, ethidium bromide, a DNA intercalating agent that provokes mtDNA depletion, reduced 3T3-L1 MT-CO1 and PPARγ mRNA levels [4].…”
Section: Resultsmentioning
confidence: 99%
“…It has been recently found that NRTIs altered nDNA methylation [41], and downregulated PPARγ and mtDNA-encoded genes expression [42]. Moreover, ethidium bromide, a DNA intercalating agent that provokes mtDNA depletion, reduced 3T3-L1 MT-CO1 and PPARγ mRNA levels [4].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is conceivable to expect that the potential cumulative side effects of NRTIs may lead to long-term tissue damage in the population aging with HIV/AIDS (13)(14)(15). In that regard, long-term therapy with zidovudine has been associated with a toxic mitochondrial myopathy (16) and myocyte mitochondrial dysfunction with increased ROS production, confirmed by both in vitro and in vivo studies (2,3,10,11,17,18).…”
mentioning
confidence: 89%
“…Mitochondria promote the abundance of SAM in both embryonic and post-natal growth conditions [100]. In heart, oxidative stress increases SAM abundance and promotes DNA methylation associated with pathological remodeling [101]. …”
Section: Dna Methylationmentioning
confidence: 99%